If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -27 + x + -9 = 360 Reorder the terms: -27 + -9 + 5x + x = 360 Combine like terms: -27 + -9 = -36 -36 + 5x + x = 360 Combine like terms: 5x + x = 6x -36 + 6x = 360 Solving -36 + 6x = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 6x = 360 + 36 Combine like terms: -36 + 36 = 0 0 + 6x = 360 + 36 6x = 360 + 36 Combine like terms: 360 + 36 = 396 6x = 396 Divide each side by '6'. x = 66 Simplifying x = 66
| 5t-1=-2(4-3t)+10 | | 238=l-3*l | | 6x+12y-30=0 | | a+16+a-18=180 | | 2x+13y=5y | | 5w-18=22 | | y=5sin(6x) | | 3m-10=50 | | 11x-10+2x+70+41=360 | | log(5x+30)=2 | | 18+00y+2y^2=0 | | t=13t+-2 | | 3r-2=4(r-2) | | 2y=-4x+7 | | X^6+2x^4-35x^2=0 | | 3x*3+7= | | 2.5x-1.5= | | 25/-5= | | 5(y-4)=7(2y-7) | | 2p^2-4p-91=5 | | 18=h+(h-6) | | 77=0.5*3+h*b | | 9v+2=3(v+4) | | 1a+2b=50 | | -3[9+(-7)]+(-5)+6= | | 5(x+7)+2=35 | | x+-11=-18 | | 3x^3+33x^2=-90 | | -3[9+(-7)]+(-5)+6=-5 | | -4.8=x-3.9 | | -3(8+7x)=-255 | | 2n-7=25n-10 |